1985
DOI: 10.1063/1.335377
|View full text |Cite
|
Sign up to set email alerts
|

Improved performance of InSe-based photoelectrochemical cells by means of a selective (photo)electrochemical etching

Abstract: It is shown that the performance of photoelectrochemical cells based on the lamellar material InSe can be considerably improved by means of a selective (photo)electrochemical etching. Whereas the cleavage Van de Waals plane (⊥ to c axis) shows little improvement, the photcurrent in the ∥ face (parallel to the c axis) is doubled (30 mA cm−2 under AM1 illumination). For n-type InSe a reverse bias (+1.5 V versus standard calomel electrode SCE) was employed during the photoetching, p-InSe electrodes were electroch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
6
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 24 publications
3
6
0
Order By: Relevance
“…In conclusion, these results are in good agreement with the literature [2,7,9,17,20,27,28]. It is seen from the experimental absorption results that the band gap of n-InSe:Ho is greater than that of n-InSe.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In conclusion, these results are in good agreement with the literature [2,7,9,17,20,27,28]. It is seen from the experimental absorption results that the band gap of n-InSe:Ho is greater than that of n-InSe.…”
Section: Resultssupporting
confidence: 92%
“…The energy gap of 1.3 eV exists at 300 K with an indirect energy gap some 50 meV below the energy of the direct gap in InSe bulk crystals [18]. There are other reports about the indirect band gap of 1.2 eV [19], and the direct band gap of 1.32 eV in InSe single crystals [9,20]. Camassel et al [7] reported an investigation of the fundamental absorption edge of InSe under high-resolution conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Anodic treatment not only leads to a chemical surface film, but also to important changes in electrode morphology. Several reports indicate that anodization of II-VI semiconductors causes surface pitting, [12][13][14][15][16][17][18][19][20][21] but the authors do not address the question of whether pores extend deeply below the surface; their work focuses on surface roughening and its important effects on the photoelectrochemical properties. Recently, we showed that anodic treatment can render p-Cd 0.95 Zn 0.05 Te porous across a thickness of more than 100 m, 22 and nanoporous layers with quantum size effects have been obtained by anodization of p-ZnTe.…”
mentioning
confidence: 99%
“…However, when 1.2 electrons/molecule was added, the X^s hifted to even longer wavelengths (beyond 2500 nm). This is preliminarily interpreted to mean that (11) Miller, L. L.; Zhong, C. J.; Kasai, P. H. Submitted for publication. (12) Heywang, G.; Bom, L; Fitzky, H.-G.; Hassel, T.; Hocker, J.;…”
mentioning
confidence: 99%